1997
DOI: 10.1590/s0004-282x1997000100009
|View full text |Cite
|
Sign up to set email alerts
|

Dados normativos para o teste de fluência verbal categoria animais em nosso meio

Abstract: RESUMO -Objetivos: Avaliar o desempenho na fluência verbal em nossa população e verificar a influência da idade e escolaridade. Métodos: Foram entrevistados 336 indivíduos sem queixas neurológicas ou psiquiátricas, através do Mini-Exame do Estado Mental (MEM) e geração de animais em um minuto. Para efeito comparativo e para verificação dos níveis de corte, foram examinados 65 indivíduos com quadro de perda cognitiva, acompanhados no ambulatório de Neurologia do Comportamento da EPM. Resultados: Na população "n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
120
2
37

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(162 citation statements)
references
References 30 publications
3
120
2
37
Order By: Relevance
“…Os resultados demonstraram que o grupo de analfabetos obteve resultados inferiores aos do grupo de escolarizados; desta forma, o analfabetismo influenciou os escores obtidos nessa escala, sugerindo que o diagnóstico de demência para a população analfabeta brasileira pode incluir falso-positivo, até porque os erros apresentados por analfabetos parecem com os encontrados em pacientes com lesão cerebral 24 .…”
Section: Discussionunclassified
“…Os resultados demonstraram que o grupo de analfabetos obteve resultados inferiores aos do grupo de escolarizados; desta forma, o analfabetismo influenciou os escores obtidos nessa escala, sugerindo que o diagnóstico de demência para a população analfabeta brasileira pode incluir falso-positivo, até porque os erros apresentados por analfabetos parecem com os encontrados em pacientes com lesão cerebral 24 .…”
Section: Discussionunclassified
“…schizophrenia, bipolar mood disorder or lifetime depressive disorder), non-corrected visual or auditory disorders, exposure to neurotoxic substances and cranioencephalic traumatism were excluded from the study. The cognitive assessment included the Cambridge Cognitive Examination (CAMCOG) 14 , Mini-Mental State Examination (MMSE) 15 , semantic verbal fluency (category animals) 16,17 , Trail Making Tests (TMT) A and B 18 and the 12-item-Boston Naming Test 19 . Behavioral evaluation was assessed by the Neuropsychiatric Inventory (NPI) 20,21 .…”
Section: Clinical and Neuropsychological Assessmentmentioning
confidence: 99%
“…These findings corroborate those of our study. On the other hand, Banhato and Nascimento 28 found no difference between participantLanguage performance was impaired in both groups; once more, intragroup comparison showed that Group 1 individuals were the most impaired and the performance in semantic fluency (Animals), an average of 8.7 and 11.9 for Groups 1 and 2, respectively, was inferior to the results found by other Brazilian studies using healthy adults 29,30 . OstroskySolis et al 4 studied the relation of the EL of normal subjects aged 16 to 85 years and education ranging from illiterate to four years of schooling and found no difference between them in the phonological fluency test (FAS) while Mansur et al 31 in a study using the Boston Naming Test, concluded that the lower the EL, the worse the performance to name.…”
Section: Discussionmentioning
confidence: 58%